1985
DOI: 10.1111/j.1365-2141.1985.tb07333.x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of patients with subtype IIb‐like von Willebrand's disease by means of perfusion experiments with reconstituted blood

Abstract: Four unrelated patients with a bleeding diathesis (bleeding time longer than 30 min), some spontaneous platelet aggregation, thrombocytopenia and large platelets, had decreased levels of factor VIII-von Willebrand factor (FVIII-VWF) related properties and impaired platelet adherence to human artery subendothelium. The largest multimers of plasma FVIII-VWF were absent and enhanced ristocetin induced platelet aggregation in platelet-rich plasma was observed. 'Pseudo-von Willebrand's disease' was excluded, becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Takahashi (23), and one other study with SPA (24). In the latter study, two patients had defects oftheir platelets and two defects in their plasma when studied in perfusion experiments (24). Holmberg et al (5) Recent studies in platelet-type vWd in Japanese patients have shown an abnormality of the GPIb, possibly explaining why the platelets of these patients adsorbed normal vWf without any agonist (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Takahashi (23), and one other study with SPA (24). In the latter study, two patients had defects oftheir platelets and two defects in their plasma when studied in perfusion experiments (24). Holmberg et al (5) Recent studies in platelet-type vWd in Japanese patients have shown an abnormality of the GPIb, possibly explaining why the platelets of these patients adsorbed normal vWf without any agonist (23).…”
Section: Discussionmentioning
confidence: 99%
“…We have previ- ously described a form of vWd similar to that described by Takahashi; however, in our binding studies we employed patients' platelets free of plasma proteins and used purified radiolabeled normal F.VIII/vWf (20). Takahashi (23), and one other study with SPA (24). In the latter study, two patients had defects oftheir platelets and two defects in their plasma when studied in perfusion experiments (24).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the only ex vivo tests that reflect vWF function are perfusion experiments with high shear forces over defined matrixes (denuded endothelium, collagen preparations). The most frequently used perfusion chambers of Baumgartner et al 38 or Sakariassen et al 39 are not suitable for routine diagnostic procedures and are therefore reserved for scientific work. With the cone and plate aggregometer, 40 defined shear forces can be applied; however, its use as a routine diagnostic instrument has not been thoroughly investigated.…”
Section: Adhesion/retentionmentioning
confidence: 99%
“…They classified it as having a pathophysiologic mechanism in common with either platelet-type VWD or type IIb VWD. Sakariassen et a1 [35] described four patients with subtype IIb VWD, two with the specific defect of intrinsic platelet abnormality, and two with a plasma defect. They concluded that subtype IIb may represent a heterogeneous group.…”
Section: Discussionmentioning
confidence: 99%